Biomechanical, Topological and Chemical Features That Influence the Implant Success of an Urogynecological Mesh: A Review. (28th April 2016) - De Maria, Carmelo; Santoro, Vito; Vozzi, Giovanni
Abstract : Synthetic meshes are normally used to treat several diseases in the field of urogynecological surgery. Not-optimal selection of mesh and/or its not-correct implant may increase patient's pain and discomfort. The knowledge of mechanical behaviour and topological and chemical properties of a mesh plays a fundamental role to minimize patient's suffering and maximize the implant success. We analysed several papers reporting the meshes application for urogynecological pathologies, to extrapolate the principal parameters that normally are used to characterise the biomechanical, topological, and chemical properties, and to verify their influence on implant success. In this way we want demonstrate that, knowing these features, it is possible to foresee the success of a mesh implant. This review shows that the application of a mesh strictly depends on elastic modulus, failure load, porosity and pore size, filament diameter, polymer weight, and crystallinity. To increase the success of the implant and to help choice of optimal mesh for a clinical need, two indexes have been proposed for comparing, in an easier way, the mechanical performance of different commercially available meshes.